Temenggung Adat dalam Menyelesaikan Sengketa Tanah Adat Suku Dayak dengan Perusahaan Kelapa Sawit Dihubungan dengan Undang-undang No 5 Tahun 1960 UUPA - Muhammad Raihan Ruddy; Lina Jamilah (UNISBA Press, 2022)
Abstract.The land is the most basic need of life, especially for indigenous peoples in remote areas who still rely on agriculture as their livelihood. The UUPA still recognizes the existence of customary land owned by indigenous peoples which are called ulayat land. The existence of communal land is recognized in Article 5 of the Basic Agrarian Law which explains that the agrarian law that applies to earth, water and space is customary law. The existence of ulayat land has been threatened with the arrival of an oil palm company that holds a Cultivation Right permit which causes the ulayat land of the Dayak tribe in Kalimantan to be eliminated because almost all of the ulayat land has not been registered, causing the rights to ulayat land to be weak, resulting in disputes that are difficult to resolve. So that it will be examined about the customary Tomenggung who have the rights and authority in resolving disputes over the customary land of the Dayak tribe which are tied to the UUPA and the consideration of the customary Tomenggung in resolving the dispute.The research uses a normative juridical approach which is based on secondary data research, in addition to research on primary data. This research is analytical descriptive, that is, it provides an overview of the customary head in customary land disputes. From the results of this study, efforts to settle amicably with the traditional Temenggung as intermediaries who have the authority to resolve a dispute with mediation efforts. The consideration of Temenggung Dayak Seruyan in resolving this dispute is the responsibility of the company for what is done to local customs. the existence of compensation to indigenous peoples is meant that land rights can be revoked, by providing appropriate compensation and according to the method regulated by law, to fulfil the requirements of the meaning of article 18 of the UUPA. Abstrak. Tanah adalah kebutuhan hidup yang paling mendasar terutama bagi masyarakat adat di daerah terpencil yang masih mengandalkan pertanian sebagai mata pencaharianya. Dalam UUPA masih diakui adanya tanah adat yang dimiliki oleh masyarakat adat yang dinamakan tanah ulayat. Keberadaan talah ulayat diakui dalam Pasal 5 Undang-Undang Pokok Agraria yang menjelaskan Hukum agraria yang berlaku atas bumi, air dan ruang angkasa ialah hukum adat. keberadaan tanah ulayat telah terancam dengan datangnya perusahaan Kelapa Sawit yang mengantongi izin Hak Guna Usaha yang menyebabkan tanah ulayat suku Dayak di Kalimantan tersingkir karena hampir seluruhnya tanah ulayat belum terdaftar menyebabkan hak atas tanah ulayat menjadi lemah Sehingga menimbulkan persengketaan yang sulit penyelesaianya. Sehingga akan diteliti mengenai Temenggung adat yang memiliki hak dan kewenangan dalam menyelesaikan sengketa tanah adat suku Dayak yang dikatikan dengan UUPA dan Pertimbangan Temenggung adat dalam menyelesaikan sengketa tersebut. Penelitian menggunakan pendekatan secara yuridis normative yang pendekatanya pada penelitian data sekunder, disamping penelitian terhadap data primer. Penelitian ini bersifat deskriptif analitis. Dari hasil penelitian ini diharpkan akan lebih memahami Upaya penyelesaian secara damai dengan Temenggung adat sebagai perantara yang memiliki kewenangan untuk menyelesaikan suatu sengketa dengan upaya mediasi. Pertimbangan Temenggung adat Dayak seruyan dalam menyelesaikan sengketa ini adalah pertanggungjawaban dari pihak perusahaan atas apa yang diperbuat terhadap adat setempat. adanya ganti rugi kepada masyarakat adat ini dimaksudkan bahwa hak-hak atas tanah dapat dicabut, dengan memberi ganti kerugian yang layak dan menurut cara yang diatur dengan Undang-undang, agar terpenuhi syarat dari makna pasal 18 UUPA.